2019
DOI: 10.12669/pjms.35.2.520
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pro-inflammatory cytokines and antimicrobial proteins in elderly women with iron deficiency anemia

Abstract: Objective: Iron Deficiency Anemia (IDA) is common nutritional deficiency particularly in women and also common during the older age. Aging increases plasma levels of inflammatory mediators such as pro-inflammatory cytokines and acute phase proteins. However, there is little information about changes in antimicrobial proteins in elderly women with IDA. In this study, we aimed to determine the changes in pro-inflammatory cytokines and newly discovered antimicrobial proteins like hepcidin, chemerin and defensin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, they saw the levels of chemerin specifically in females with iron deficiency anemia. 21 Given the difference in in vitro results regarding chemerin and bone new observational studies in human are important to explore the definitive role of chemerin in bone homeostasis. Our study bridges this gap and provides an insight in bone homeostasis, which may be context-specific, and elaborates role of chemerin in relation to bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, they saw the levels of chemerin specifically in females with iron deficiency anemia. 21 Given the difference in in vitro results regarding chemerin and bone new observational studies in human are important to explore the definitive role of chemerin in bone homeostasis. Our study bridges this gap and provides an insight in bone homeostasis, which may be context-specific, and elaborates role of chemerin in relation to bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…IDA is a condition that occurs among children in both developing and developed countries, leading to impaired development, activity intolerance, behavioural changes, irritability, and reduced learning ability; women and elderly individuals are also affected [45,46]. The iron deficiency associated with IDA can be classified as either absolute or functional iron deficiency: absolute iron deficiency is defined as a severe reduction in or loss of iron reserves in the bone marrow, liver, and spleen, while functional iron deficiency is defined as deficiency due to inadequate intake, malabsorption, or metabolic disorders [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Askar et al [21] demonstrated that pro-inflammatory cytokines, such as TNF-α and interleukin-6, antimicrobial proteins, such as hepcidin, defensin, and chemerin, acute phase reactants, such as C-reactive protein, were elevated in older patients with IDA. The investigators noted that both aging and IDA might affect pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%